Հայ հոգևոր հայրերի սրբացումը գերմանական հողերում - Անուշ Արշակյան (ՀՀ ԳԱԱ հրատ.)
Информация о существенной роли отдельных армян в деле распространения христианства, а также об их стране широко распространялась в германских землях через церковные писания. В средние века преобладающим направлением в «миграционной географии» было перемещение священных реликвий с юга на север, в края, богатые святыми и ранней христианской героической историей: Армения, регионы средиземноморской и латинской Европы. Христианские духовные отцы из Армении – Аврелий, Влас и Серватия – в средние века обожествлялись в германских землях, и все еще живой культ армянских святых в Германии является своего рода мостом между древней христианской Арменией и Центральной Европой. The information about the essential role of individual Armenians in the spreading Christianity and also about their country were widely distributed in the German lands through the scriptures. In the Middle Ages the prevailing direction in “migration geography” was moving the sacred relics from south to north – territories – rich in saints and heroic history of the early Christian: Armenia, the regions of the Mediterranean and Latin Europe. The Christian spiritual fathers–natives of Armenia –Aurelius, Vlas and Servatius, were idodized in the Middle Ages in the German lands. And still alive is the cult of Armenian saints in Germany: it is a kind of bridge between the ancient Christian Armenia and Central Europe.
Keywords: History; B Philosophy; Psychology; Religion; Medieval History; BR Christianity; D History